2021
DOI: 10.21037/apm-21-2750
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the functional connectivity characteristics of brain networks in post-stroke patients with global aphasia: a healthy control based resting-state fMRI study

Abstract: Background: In this study, resting-state functional magnetic resonance imaging (rs-fMRI) was used to investigate the characteristics of functional connectivity of brain networks in patients with post-stroke global aphasia (PGA).Methods: PGA patients hospitalized in Wuxi Tongren Rehabilitation Hospital during their subacute stage were selected as a case group, and healthy volunteers with matching age, sex, and education level were selected as healthy controls (HCs). rs-fMRI scans were performed to compare the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…PSCI highlights the causal relationship between stroke and cognitive impairment. Brain network connections have shown dynamic changes throughout stroke [ 6 ]. Many studies have found that alterations of FC and SC within and between brain RSNs correlate with cognitive decline and recovery after a stroke exposure [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…PSCI highlights the causal relationship between stroke and cognitive impairment. Brain network connections have shown dynamic changes throughout stroke [ 6 ]. Many studies have found that alterations of FC and SC within and between brain RSNs correlate with cognitive decline and recovery after a stroke exposure [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recovery of the lexical-semantic system was associated predominantly with the activations of these regions (12). Resting-state fMRI (rs-fMRI) showed that patients with global aphasia had decreased interhemispheric and intra-hemispheric connectivity and enhanced connection between language network and cerebellar structures (13). These studies show that the utilization of neuroimaging techniques is feasible for research on global aphasia.…”
Section: Introductionmentioning
confidence: 86%
“…The conventional FC network is usually constructed based on the pairwise correlation among different brain regions (Agoalikum et al, 2021 ; Z. J. Feng, Deng, et al, 2021 ; Liu et al, 2022 ; Xu et al, 2021 ). However, we have reasons to believe that the connections between brain regions in real neural networks are intricate and not just pairwise (Jie et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%